Hardship and Vulnerability in the Pacific Island Countries : A Regional Companion to the World Development Report 2014 - World Bank (Washington, DC, 2014)
In many Pacific island countries, meeting non-food basic needs is a growing challenge and further complicated by substantial economic and environmental risks. Hardship and vulnerability are increasingly prominent concerns in Pacific island countries, but the knowledge base to guide policymaking is limited. Family and community networks are central to life in most Pacific island countries, providing critical support to members in need and acting as safety nets when individuals or households experience losses from shocks. The primary objective of this report is to present solid empirical evidence of hardship, vulnerability to shocks, and risk management in the Pacific region. The report is primarily a stocktaking exercise that brings together existing evidence and new analysis of available data using a consistent framework. The report takes a "micro" perspective that of the individual and household but accounts for the important role of communities, the state, and international partners. This report focuses on risks, but accounts for the role of opportunities when possible. While remaining supportive of viable economic growth sectors, given the limited means of most Pacific governments, expenditure should be carefully focused on investments with high expected economic returns and relatively low risks. Development partners can play a role in financing these investments and in sharing experiences on what works from other parts of the world.